Solidaritas dan Integrasi Sosial dalam Konteks Manajemen Pendidikan: Analisis Berdasarkan Teori Émile Durkheim - Almuarif Almuarif; Silfia Hanani; Indra Devi; Aisyah Syafitri (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
The concepts of solidarity and social integration play an important role in creating an effective learning environment. They form the basis of learning, character building and preparing students to play an active role in an increasingly complex society. The purpose of this research is to explain about Solidarity and Social Integration in the Context of Education Management: An Analysis Based on Émile Durkheim's Theory. The method used in this study uses qualitative research procedures using a research approach in the form of a literature study. The sources of information in this study were reviewed from various novel sources of literature, research reports, scientific essays, theses, dissertations and posts both print and electronic related to Solidarity and Social Integration in the Context of Education Management: An Analysis Based on Émile Durkheim's Theory. The results of this study suggest that an understanding of solidarity and social integration in the context of Durkheimian theory is important. These concepts help guide approaches and practices that promote a balance between uniformity and diversity, respect for shared social norms, and understanding of the unique role of individuals in achieving common goals. Education, as a key tool in shaping society, plays an important role in facilitating social integration and creating solidarity. In education management, curriculum development, student participation, collaboration between stakeholders, inclusive approaches, and an understanding of the role of education in social integration are key in achieving this goal.